2013
DOI: 10.1002/glia.22568
|View full text |Cite
|
Sign up to set email alerts
|

Role of connexin 32 hemichannels in the release of ATP from peripheral nerves

Abstract: Extracellular purines elicit strong signals in the nervous system. Adenosine-5'-triphosphate (ATP) does not spontaneously cross the plasma membrane, and nervous cells secrete ATP by exocytosis or through plasma membrane proteins such as connexin hemichannels. Using a combination of imaging, luminescence and electrophysiological techniques, we explored the possibility that Connexin 32 (Cx32), expressed in Schwann cells (SCs) myelinating the peripheral nervous system could be an important source of ATP in periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 73 publications
2
30
0
Order By: Relevance
“…The positive potentials required for Panx1 channel activation approximate the reversal potential for MgATP 2− and ATP 4− . Indeed, as indicated in a recent study of connexin hemichannels (38), a membrane potential of +80 mV is close to or even beyond the reversal potential for ATP. ATP flux through connexin hemichannels, which only open at extreme positive potentials, did not occur while the membrane potential was stepped to +80 mV.…”
Section: Discussionmentioning
confidence: 74%
“…The positive potentials required for Panx1 channel activation approximate the reversal potential for MgATP 2− and ATP 4− . Indeed, as indicated in a recent study of connexin hemichannels (38), a membrane potential of +80 mV is close to or even beyond the reversal potential for ATP. ATP flux through connexin hemichannels, which only open at extreme positive potentials, did not occur while the membrane potential was stepped to +80 mV.…”
Section: Discussionmentioning
confidence: 74%
“…Such a critical molecule, if one exists, remains to be identified. However, one candidate is ATP, the release of which appears to be dependent on Cx32 hemichannels and is likely affected by mutations in GJB156. In this regard, this study has shown that the four PNS-only mutations, if they indeed obstruct the flux of larger molecules, could be useful in future studies aimed at determining which small molecules could be relevant to CMT1X pathology in peripheral nerve.…”
Section: Discussionmentioning
confidence: 88%
“…Very little is known about how Schwann cells influence the activity of sympathetic axons in the periphery. What is known suggests that myelinating Schwann cells do share some common features with enteric glia such as the expression of Sox10 and the ability to release neuroactive substances like ATP through hemichannels (Nualart-Marti et al 2013). However, there are also important differences between the specific mechanisms used by the two cell types.…”
Section: Discussionmentioning
confidence: 99%